2x - y = 6
3x + y = 14
Answers
Answered by
2
2x-y = 6
3x+y = 14
5x=20
x= 4
2x-y=6
2(4)-y=6
8-y=6
y=2
3x+y = 14
5x=20
x= 4
2x-y=6
2(4)-y=6
8-y=6
y=2
shaiksalman580:
plzz mark it as brainliest answer if it helped u
Answered by
0
hello users ....
Given equations are :
2x - y = 6 ........(1.)
3x + y = 14 ......(2.)
solution:-
Adding equations (1.) and (2.)
we get
2x - y = 6
+ 3x + y = 14
----------------------
5x + 0 = 20
----------------------
=> 5x = 20
=> x = 20 / 5 = 4
putting x in equation (1.)
we get
2×4 - y = 6
=> 8 - y = 6
=> -y = 6 - 8
=> -y = - 2
=> y = 2
Hence ,
x = 4 and y = 2 Answer
# hoe it helps :)
Given equations are :
2x - y = 6 ........(1.)
3x + y = 14 ......(2.)
solution:-
Adding equations (1.) and (2.)
we get
2x - y = 6
+ 3x + y = 14
----------------------
5x + 0 = 20
----------------------
=> 5x = 20
=> x = 20 / 5 = 4
putting x in equation (1.)
we get
2×4 - y = 6
=> 8 - y = 6
=> -y = 6 - 8
=> -y = - 2
=> y = 2
Hence ,
x = 4 and y = 2 Answer
# hoe it helps :)
Similar questions